The use of continuous foetal monitoring technologies that enable mobility in labour for women with complex pregnancies: A survey of Australian and New Zealand hospitals. (February 2021) - Fox, Deborah; Maude, Robyn; Coddington, Rebecca; Woodworth, Rachael; Scarf, Vanessa; Watson, Kylie; Foureur, Maralyn
Highlights: This is the first survey of the use of continuous foetal monitoring technologies in Australian and New Zealand hospitals Wireless technology was seen to increase women's mobility and a sense of choice and control in labour Most Australian and New Zealand facilities have wireless machines, however barriers to women's access persist Reasons for barriers to access are unclear, further research is required Abstract: Objective: Freedom of movement and choice of positioning in labour and birth is known to enhance physiological processes and positive experiences for women during childbirth. Continuous foetal monitoring technologies that enable mobility in labour for women with complex pregnancies, such as wireless CTG, have been marketed for clinical use in most high resource settings since 2003 but there is a paucity of midwifery literature about its clinical use. The aim of this survey was to determine how often, and for whom, wireless and beltless technologies are being used in maternity settings across Australia and New Zealand and to identify any barriers to their uptake. Design: A survey tool developed by Watson et al. (2018) for use in the United Kingdom was adapted for the Australian/New Zealand context. One Maternity Unit Manager or key midwifery clinician from each of 208 public and private hospitals across Australia and New Zealand was invited by email to participate in an online survey between October 2019 and January 2020. Descriptive statistics were used to describe the characteristics of the facilities and the frequency of availability of the monitors. Free text responses were thematically analysed. Findings: The survey received a high (71%) response rate from a range of public and private hospitals in urban and rural settings. Women's freedom of movement and sense of choice and control in labour were seen by most respondents to be positively influenced by wireless monitoring technology. Most facilities reported having at least one wireless or beltless foetal monitor available, however, results suggest that many women consenting to continuous monitoring still do not have access to technology that enables freedom of movement. Keyconclusions: Further research is required to explore the barriers and facilitators to enabling freedom of movement and positioning to all women in childbirth, including those women with complex pregnancies who may consent to continuous foetal monitoring.